Breakfast: The most important meal of the day? - Spence, C (Elsevier, 2017)
Stating the obvious, we typically eat different foods at different times of day. But why should that be so? While much of this variation is likely down to cultural factors, the dietitians also have plenty to say on the matter of what we should be eating and drinking when, in order, for instance, to lose weight, or else to help enhance our cognitive performance during the course of the day. In recent years, many of the larger food companies have become increasingly interested in trying either to break into the profitable, not to mention growing, market for breakfast foods, or else to figure out how to convince more consumers to eat ‘breakfast foods’ at other times of day. In this review, I want to take a closer look at the psychological science behind the first meal of the day, highlighting why it may be even more important than most people think – both to the consumer but also the food industry more generally. Finally, I summarize a number of the current trends in the kinds of breakfast items that are becoming more/less popular, and consider what may be driving them.